Workplace Bullying and Medically Certified Sickness Absence: Direction of Associations and the Moderating Role of Leader Behavior - Nielsen, Morten Birkeland; Indregard, Anne-Marthe Rustad; Krane, Line; Knardahl, Stein (Frontiers in Psychology, 2019)
The aim of this study was to determine 1) associations between workplace bullying and subsequent risk and duration of medically certified sickness absence, 2) whether employees’ perceptions of supportive, fair, and empowering leader behavior moderate the association between bullying and absence, and 3) whether prior sickness absence increases the risk of being a new victim of bullying. Altogether 10,691 employees were recruited from 96 Norwegian organizations in the period 2004 to 2014. The study design was prospective with workplace bullying and leader behavior measured at baseline, and then linked to official registry data on medically certified sickness absence for the year following the survey assessment. For analyses of reverse associations, exposure to bullying was reassessed in a follow-up survey after 24 months. The findings showed that workplace bullying was significantly associated with risk (Risk Ratio =1.23; 95% CI=1.13 – 1.34), but not duration (Incidence Rate Ratio=1.05; 95% CI=.89 – 1.25) of medically certified sickness absence after adjusting for age, gender, and supportive, fair, and empowering leader behavior. None of the indicators of leader behavior moderated the association between bullying and sickness absence (both risk and duration). Adjusting for baseline bullying, age and gender, prior long-term sickness absence (>21 days) was associated with increased risk of being a new victim of bullying at follow-up (Odds Ratio=1.86; 95% CI=1.28 – 2.72). Effective interventions towards workplace bullying may be beneficial with regard to reducing sickness absence rates. Organizations should be aware that long-term sickness absence might be a social stigma as sick-listed employees have an increased risk of being bullied when they return to work.